Scenarios for Economic Recovery: The Philippines - Mario B. Lamberte; Josef T. Yap (Philippine Institute for Development Studies (PIDS), 1999)
This study reviews the economic policies and performance of the Philippine economy in the 1990s, briefly assesses the macro- and microeconomic impacts of the Asian financial crisis, describes the measures adopted by the government in response to the Asian financial crisis, and discusses the direction of the recovery and development of the economy in the short, medium and long term. It draws up short-term action plans, which the government could immediately initiate and complete within two years, to spur economic recovery. It also proposes medium- and long-term action plans to continue the restructuring of the economy and sustain the growth momentum. Towards the end, the study outlines the role of donor agencies in supporting the government's efforts to spur economic growth in the short term and achieve a sustainable growth in the long term.
Keywords: 330; economic recovery; Asian financial crisis